A Modified Design of the Pectoralis Major Myocutaneous Flap for Reconstruction of Head and Neck Defect. Issue 5 (July 2021) - Lyu, Xiaoming; Liu, Shuming; Zheng, Lei; Huang, Mingwei; Zhang, Jianguo; Zhang, Jie
Abstract : Abstract: Even though the pectoralis major myocutaneous flap (PMMF) still has an important role in the free flaps ear, it is reported to have drawbacks such as the limited cephalad extension and high incidence of total or partial flap necrosis. Various modifications have been attempted to augment the limited cephalad extension and a stable blood supply. The aim of this study is to describe a modified design of the skin paddle and preparation of the PMMF, to achieve stable blood circulation and sufficient pedicle length. The priority skin paddle is the medial part for its stable blood supply, and the lateral margin should be adjusted as needed. During the harvesting, the lateral thoracic artery (LTA) is preserved to protect the perforating branches, and the anterior sheath of the rectus abdominis muscle is used as a suture margin to prevent damage of the thin muscle of the PMMF. The skin paddles in this study are larger than those previously reported. All of the 21 patients in our study, the skin paddles show complete survival with no partial necrosis of skin paddle, fistula, or wound dehiscence. It is worthwhile to consider and preserve the LTA as a major contributor to a lateral and distal PMMF. This study would be useful in future and preparation of the PMMF in head and neck reconstruction. Abstract : Supplemental Digital Content is available in the text